1995
DOI: 10.1111/j.1365-2265.1995.tb01876.x
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of hypogonadism to the development of osteoporosis in thalassaemia major: new therapeutic approaches

Abstract: Hypogonadism seems to play an important role in the development of osteopenia-osteoporosis in thalassaemia major; continuous hormone replacement therapy with transdermal oestrogen for females or hCG for responding males best improves the bone density parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
78
3
10

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 29 publications
10
78
3
10
Order By: Relevance
“…This suggests that an important determinant of the often suboptimal bone response to testosterone replacement reported previously may be inadequate prior testosterone treatment, largely due to the pharmacological limitations and inconvenience of the available testosterone products. Our findings on the bone density benefits of sustained, adequate treatment are consistent with findings that AD thalassaemic adolescents taking regular testosterone treatment had higher BMD than others whose testosterone treatment was irregular (42,43). In most previous longer (.…”
Section: Discussionsupporting
confidence: 80%
“…This suggests that an important determinant of the often suboptimal bone response to testosterone replacement reported previously may be inadequate prior testosterone treatment, largely due to the pharmacological limitations and inconvenience of the available testosterone products. Our findings on the bone density benefits of sustained, adequate treatment are consistent with findings that AD thalassaemic adolescents taking regular testosterone treatment had higher BMD than others whose testosterone treatment was irregular (42,43). In most previous longer (.…”
Section: Discussionsupporting
confidence: 80%
“…Delayed or arrested puberty is common in patients with thalassaemia (4, 5) because of disturbed gonadotrophin-releasing hormone secretion (5, 34) with consequent deficiency of sex steroids. Sex steroids can influence growth through the modulation of IGF-Iinduced cellular response (35)(36)(37), and their deficiency adds significantly to the growth delay and osteoporosis of thalassaemic children (38). This may explain the relatively short upper segment, in addition to the mild vertebral changes observed in our thalassaemic group.…”
Section: Discussionmentioning
confidence: 69%
“…[1][2][3][4][5] Bone problems may be present even in welltransfused and chelated patients. Various factors contribute to the development of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have been performed using dual energy X-ray absorptiometry (DEXA) to measure bone mineral density (BMD) in patients with transfusion-dependent thalassaemia. [1][2][3][4][5] The prevalence of reduced BMD varied, but Jensen et al 1 reported that half of their 82 patients had severely low BMD whereas the other 45% had low bone mass. Angastiniotis et al 5 showed that patients with thalassaemia intermedia were not spared, and 75% of them had BMD below À2 s.d.…”
mentioning
confidence: 99%